1995
DOI: 10.1038/hdy.1995.90
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mapping in Pinus pinaster (maritime pine) using RAPD and protein markers

Abstract: A detailed genomic map was constructed for one F1 individual of maritime pine, using randomly amplified polymorphic DNA (RAPD) and protein markers scored on megagametophytes of germinated seeds. Proteins allowed the localization of exclusively coding DNA in the large genome of this Pinus species, mapped with RAPD markers that essentially fail within repetitive (i.e. mostly noncoding) DNA. Dot blots experiments of 53 RAPD fragments showed that 89 per cent amplified from highly repetitive chromosomal regions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 37 publications
3
41
0
5
Order By: Relevance
“…These authors identified 9 QTLs explaining between 2.79 and 8.11% of the phenotypic variance of rooting ability, with 5 being detected in two consecutive years and 4 being specific to only one year. In maritime pine (C. Plomion, unpublished data), only one strong QTL was detected on linkage group 6 of the map described by Plomion et al [25,26], explaining a high percentage (18.7%) of the phenotypic variance.…”
Section: Qtl Detectionmentioning
confidence: 96%
“…These authors identified 9 QTLs explaining between 2.79 and 8.11% of the phenotypic variance of rooting ability, with 5 being detected in two consecutive years and 4 being specific to only one year. In maritime pine (C. Plomion, unpublished data), only one strong QTL was detected on linkage group 6 of the map described by Plomion et al [25,26], explaining a high percentage (18.7%) of the phenotypic variance.…”
Section: Qtl Detectionmentioning
confidence: 96%
“…The 22.3 % of segregation distortion detected can be due to band co-migration, on which two or more different loci generate bands of a similar or same size (Plomion et al 1995). Studies in the same species have detected up to 34 % of segregation distortion (Kuang et al 1999), however the smaller number of offspring compared to earlier studies (Wilcox et al 2001, Devey et al 2004 could be responsible for the low representativeness of the expected allelic proportions.…”
Section: Resultsmentioning
confidence: 89%
“…The gels were simultaneously run and silverstained according to Damerval et al (1987) in the apparatus described by Granier and de Vienne (1986 (fig 1). In a haploid progeny we observed the 1:1 segregation ratio for presence and absence of a spot (Plomion et al, 1995b).…”
Section: Introductionmentioning
confidence: 84%
“…Although RFLPs are almost unlimited in number, they require elaborate laboratory techniques, which makes them labor intensive, timeconsuming and costly (Kesseli et al, 1994). In addition, DNA content is so high in Pinaceae (Ohri and Khoshoo, 1986;Wakamiya et al, 1993) Menozzi, 1993, 1995) and for genetic mapping (Plomion et al, 1995b (Tulsieram et al, 1992;Nelson et al, 1993;Binelli and Bucci, 1994;Plomion et al, 1995a), or when RAPD primers are screened for informative markers segregating 1:1 in diploid tissues (Carlson et al, 1991;Kubisiak et al, 1995). However, the conifer genome is characterized by a high proportion of repetitive DNA (Miksche and Hotta, 1973;Rake et al, 1980;Kriebel, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation